Multi-project programmes functions, forms and implications for evaluation and learning - and Buffardi, Anne; Hearn, Simon (Methods Lab, 2015)
Multi-project programmes can serve different purposes. For instance, they may coordinate multiple implementing entities; standardise management and technical support; compare intervention approaches across different contexts; enhance leverage through joint action; or foster sustainability by building relationships among organisations. At the same time, multi-project programmes are costly, potentially duplicate other mechanisms that fulfil similar functions, and can dilute focus and create confusion. To guide decisions on what coordination, evaluation and learning mechanisms are needed, it is helpful to articulate the intended purpose of using a programme model. Identifying the purpose(s) can help staff determine what types of knowledge sharing strategies may be most useful to the programme, and how project and programme theories of change can be sequenced